2010
DOI: 10.1094/pdis-94-8-0993
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Pathological Diversity Among Xanthomonas Strains Responsible for Bacterial Spot on Tomato and Pepper in the Southwest Indian Ocean Region

Abstract: Bacterial spot of tomato and pepper, a major problem in tropical climates, can be caused by several Xanthomonas genospecies. We examined the genetic and pathological diversity of a collection of 72 strains from the southwest Indian Ocean region as part of a regional research and development program to update inventories of agricultural pests and pathogens. Xanthomonas euvesicatoria, X. perforans, X. gardneri, and X. vesicatoria were identified in our strain collection. The identification of strains at the spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 46 publications
3
51
0
1
Order By: Relevance
“…The assays were developed with isolates from various geographic regions and subsequently validated with Brazilian isolates, though did not include any Australian isolates (Araujo et al 2012). MLSA of four genes resolved Australian BLS-causing isolates in species clades consistent with the literature (Hamza et al 2010) and distinguished them from non-pathogenic strains. The presence of Xanthomonas spp.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The assays were developed with isolates from various geographic regions and subsequently validated with Brazilian isolates, though did not include any Australian isolates (Araujo et al 2012). MLSA of four genes resolved Australian BLS-causing isolates in species clades consistent with the literature (Hamza et al 2010) and distinguished them from non-pathogenic strains. The presence of Xanthomonas spp.…”
Section: Discussionsupporting
confidence: 76%
“…atpD, dnaK, efp, and gyrB genes (supplementary Table 3) available on GenBank (Benson et al 2005) using clustalW (Larkin et al 2007). Sequences from Hamza et al (2010Hamza et al ( , 2012 and the top BLASTn hit for each gene of isolates in unresolved clades were included in the MLSA analysis. The outgroup taxa were Stenotrophomonas maltophilia, X. albilineans and X. campestris pv.…”
Section: Biochemical Analysis and Pathogenicitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, comparisons of commercially sequenced PCR products amplified from selected housekeeping gene loci now offer equivalent resolution with significantly reduced cost and effort. For example, single gene sequencing methods of Parkinson et al (2009) and multilocus sequencing methods of Young et al (2008) and Hamza et al (2010) have been shown to adequately distinguish strains of X. gardneri, X. vesicatoria, X. euvesicatoria and X. perforans. Procedures are described in the EPPO Standard PM 7/XXX on DNA barcoding as an identification tool for plant pests (in preparation).…”
Section: Dna Barcoding Methodsmentioning
confidence: 99%
“…vesicatoria is no longer a valid name (Bull et al, 2010). However, recent phylogenetic analyses based on DNA sequence similarity between single and multiple gene loci (Young et al, 2008;Parkinson et al, 2009;Hamza et al, 2010) support three distinct species, showing X. euvesicatoria and X. perforans to be highly related to (if not synonymous with) each other and also with the recently described X. alfalfa. Furthermore, X. gardneri was found to be synonymous with the established X. hortorum and the more recently described X. cynarae.…”
Section: Introductionmentioning
confidence: 92%